Property prices in Singapore. - Chye, Kok Cheong. (2013)
Over the past few years, the housing market in Singapore, especially the private market, has been growing by leaps and bounds. The number of private housing and condominium projects are on the rise, with land parcels trading at way above bench-mark prices. This express demand has also fuelled the rise and volume of HDB resale flats. Everyone seems to be eyeing a piece of private property, hoping to benefit from a possible capital appreciation.